Analyzing Advertising Specimen within the Scope of Circumstantial Choices: A Case Study of Airtel® Advertisements - Taofeek Olaiwola Dalamu (Universitas Cokroaminoto Palopo, 2018)
This study focused on the Airtel’s Always On slogan to elucidate alternating choices constructed to build strong relationships with subscribers. The proceeding semiotic paradigms were strategic discourses communicated to dominate some facets of human endeavors serving, perhaps, as signals to operational capacities of Airtel®. Halliday’s concepts of the Paradigmatic Order and Circumstantial facilities of the Transitivity system were applied to seven ads of the Always On to assist in deriving both structural and semantic values from the switching linguistic elements. Tables and a graph provided supports for the analysis as indicators of the recurring components of the analyzed structural choices. The study showed that Always On is synonymous with Airtel in terms of operational consistency. It revealed further that creativity was not limited to the phrases proceeding Always On but that the choice inventions were extended to background images playing supportive roles in the persuasion. The Circumstantial functioned as cause, manner and role with reliable service provisions. The switches provided recipients avenues to generate diverse meaning potential that could naturally stimulate individuals to consumption. The study concluded that the alternating devices did not only fascinate persuasion but also demonstrated systemic creativity of enlightenment.